INCOME ANALYSIS OF LAYING HEN FARMING BUSINESS GIVEN DIFFERENT FEED MIXTURES - S. F., Syach; Sukanata, I W.; Astawa, I P. A. (Jurnal Peternakan Tropika, 2024)
This research aims to determine the income of layer chicken farming businesses provided with different mixed ration feeds. The experimental design employed in this study was a Completely Randomized Design (CRD) with four treatments and four replications 400 involving 160 chickens. The four treatments were as follows: P0: chickens fed commercial feed (composition A), P1: chickens fed mixed ration (composition B), P2: chickens fed mixed ration (composition C), and P3: chickens fed mixed ration (composition D). The results of this research reveal that feeding with ration P1 resulted in the highest income and business income efficiency among the treatments. During the 30 days egg production period, treatment P1 yielded a net income of Rp. 268.553. Furthermore, this research also identified the break-even points for each treatment. Treatment P0 would reach the break-even point if egg production reached 584 eggs or if the egg price reached Rp. 1.148 per egg, with a total sales of Rp. 670.356 during that period. Treatments P1, P2, and P3 each had break-even points at sales of Rp. 506.057, Rp. 566.409, and Rp. 569.385, respectively, or when the egg price was Rp. 1.063, Rp. 1.102, Rp. 1.098, respectively, or when egg production reached 476 eggs, 514 eggs, 519 eggs, respectively.These findings provide valuable insights for farmers in planning the right feed strategies to enhance income efficiency and optimize profits in layer chicken farming businesses.